The Impact of Management by wandering Around on the Perception of Organizational Justice from the Perspective of Employees in the Directorates of the Jordanian Ministry of Education - Obeidat, Ahmad Abdallah; Aba Zaid, Riad Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
The aim of this study was to determine the effect of management by wandering around (MBWA) on the sense of organizational justice from the perspective of employees of the Jordanian Ministry of Education, and to identify the impact of the dimensions of management by wandering (improving communication, discovering facts, motivation, development and creativity, and feedback) on organizational justice. To achieve this purpose, the descriptive analytical method was used by collecting data through reviewing previous studies and literature and building a questionnaire consisting of forty-two questions distributed across 8 areas. After ensuring its validity and reliability, it was distributed to a sample of 229 employees working in the Jordanian Ministry of Education and its directorates in February and March 2023. After analyzing the data and testing the hypotheses, the study reached several results, including that the degree of practice of managers and department heads to management by wandering around in the directorates affiliated with the Ministry of Education, from the perspective of employees, came with a high degree of agreement. The study also found that employees' sense of organizational justice was moderate, and that there was a statistically significant effect between management by wandering around and its dimensions (improving communication, discovering facts, motivation, development and creativity, and feedback) and employees' sense of organizational justice. The study concluded with a set of recommendations, including the provision of continuous training and development for managers and department heads responsible for wandering, providing them with the necessary information and tools to ensure effective implementation of wandering, and enhancing the concept of organizational justice and its importance in building the culture of the institution.
Keywords: Management by wandering around; organizational justice; procedural justice; distributive justice; interactional justice; Ministry of Education